Poultry Eco-Controls: Performance and Accounting - Valquíria D. V. Rodrigues; Alcido E. Wander; Fabricia S. da Rosa (Agriculture, 2025)
This study aims to evaluate environmental performance indicators and eco-controls in the poultry production chain in Goiás, with a focus on forest management, waste generation, water resources, energy use, emissions, and environmental accounting. A mixed-methods approach was used, combining qualitative and quantitative data from 13 agro-industrial companies, 230 farms, and 816 broiler houses. The results highlight the role of environmental management accounting (EMA) in monitoring and improving environmental practices, supporting continuous performance assessment. Econometric analysis revealed a positive link between sustainability practices and economic growth, as measured by GDP per capita. However, productive capacity and energy efficiency showed no significant impact at the 5% level. The study limitations include the focus on a single region and industry, which may limit the generalizability of the findings. Future research should expand to other chains and regions to assess broader applicability and explore the public policy impacts on environmental sustainability, as well as the impact of public policies on environmental sustainability within the sector.